PRACTICE OF FINANCING AGRICULTURAL AGROTECHNOLOGIES IMPROVING (World Conference on Agricultural and Earth Sciences, 2026)
Agriculture remains one of the most important sectors of the global economy, playing a crucial role in ensuring food security, creating employment opportunities, and supporting sustainable economic development. The rapid development of innovative agricultural technologies has significantly transformed agricultural production by increasing productivity, improving product quality, reducing environmental impacts, and promoting efficient resource utilization. Despite these advantages, many agricultural producers, especially small and medium-sized farms, continue to experience financial constraints that limit their ability to adopt modern agrotechnologies. Therefore, improving the practice of financing agricultural agrotechnologies has become a strategic priority for governments, financial institutions, and international development organizations.
Keywords: agricultural finance, agrotechnologies, agricultural innovation, financial mechanisms, investment, agricultural insurance, digital finance, sustainable agriculture, green finance, rural development.